2018
DOI: 10.1038/s41467-017-02324-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a one-dimensional thermodynamic phase diagram for simple glass-formers

Abstract: Glass formers show motional processes over an extremely broad range of timescales, covering more than ten orders of magnitude, meaning that a full understanding of the glass transition needs to comprise this tremendous range in timescales. Here we report simultaneous dielectric and neutron spectroscopy investigations of three glass-forming liquids, probing in a single experiment the full range of dynamics. For two van der Waals liquids, we locate in the pressure–temperature phase diagram lines of identical dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 45 publications
8
65
1
Order By: Relevance
“…This observation supports the idea of identifying possible isomorphs by isochrones, an approach that was also taken studying the ultraviscous liquid in Ref. 25. The IN5 neutron spectra are shown in Fig.…”
Section: B Van Der Waals Liquid -Ppesupporting
confidence: 84%
See 1 more Smart Citation
“…This observation supports the idea of identifying possible isomorphs by isochrones, an approach that was also taken studying the ultraviscous liquid in Ref. 25. The IN5 neutron spectra are shown in Fig.…”
Section: B Van Der Waals Liquid -Ppesupporting
confidence: 84%
“…In a recent paper, we showed that the picosecond dynamics along the glass transition as a function of temperature and pressure, i.e. fast relaxations and vibrations that are completely separated from the α-relaxation, measured with neutron spectroscopy were invariant for two simple van der Waals liquids 25 . For these simple liquids, we observed isochronal superposition of the dynamics separated by 14 orders of magnitude, which was interpreted as a genuine signature of these liquids having isomorphs.…”
Section: Introductionmentioning
confidence: 99%
“…28 In particular, it is not restricted to inverse-power potentials or even to pair potentials, and several molecular systems have been shown to conform to the isomorph theory in computer simulations 32,33 and experiments. [34][35][36] Not all systems have isomorphs, though. While most metals and van der Waals bonded liquids are believed to have isomorphs in the condensed-phase part of their phase diagram, systems with significant directional bonding like covalently or hydrogen-bonded systems are not expected to have isomorphs.…”
mentioning
confidence: 99%
“…We next examine how fast the curves obtained above at finite dimension converge towards the analytical prediction of Eqs. (9) - (16). In order to investigate the deviations from the infinite-dimensional (R, γ) diagram, we quantify the deviation by subtracting the d → ∞ curve from the finite-d one, γ d (R) − γ ∞ (R), in which γ d (R) is isochore dependent and γ ∞ (R) is obtained from Eq.…”
Section: Dimensional Dependence Of the γ(R) Relationshipmentioning
confidence: 99%